Traditional Chinese medicine (Xielikang) reduces diarrhea symptoms in acquired immune deficiency syndrome (AIDS) patients by regulating the intestinal microbiota - Meng, Pengfei; Zhang, Guichun; Ma, Xiuxia; Ding, Xue; Song, Xiyuan; Dang, Shuyuan; Yang, Ruihan; Xu, Liran (Frontiers in Microbiology, 2024)
Diarrheal acquired immune deficiency syndrome (AIDS) seriously affects the quality of life of patients. In this study, we analyzed the differences in the intestinal microbiota among healthy individuals, AIDS patients without diarrhea and AIDS patients with diarrhea through high-throughput sequencing. The microbial diversity in the intestines of patients in the AIDS diarrhea group was significantly increased, and after treatment with Xielikang, the intestinal microbial diversity returned to the baseline level. At the phylum level, compared those in to the healthy (ZC) and AIDS non diarrhea (FN) groups, the relative abundances of Bacteroidetes and Verrucomirobia in the AIDS diarrhea (FA) group before treatment were significantly increased, while the relative abundance of Firmicutes was significantly decreased. Similarly, compared with those in the FA group, the relative abundances of Bacteroidea and Firmicutes in the AIDS diarrhea (FB) group after treatment were significantly increased, while the relative abundance of Firmicutes was significantly decreased after treatment. Additionally, there was no significant difference between the ZC and FN groups. At the genus level, compared with those in the ZC group, the relative abundance of Prevotella and Escherichia_Shigella in the FA group was significantly increased, while the relative abundances of Megamonas and Bifidobacterium was significantly decreased compared to that in the ZC group. After treatment with Xielikang, the relative abundance of Prevotella and Escherichia_Shigella in the FB group were significantly decreased, while the relative abundances of Megamonas and Bifidobacteria were significantly increased than those in the FA group; moreover, there was no significant difference between the ZC and FN groups. The functional prediction results showed that the ketodeoxyoctonate (Kdo) transfer to lipid IVA III and the superpathway of N-acetylglucosamine pathways in the AIDS diarrhea group were significantly altered. The correlation analysis results showed that Dorea was positively correlated with inflammatory factors, while Streptococcus and Lactobacillus were negatively correlated with inflammatory factors. The composition and function of the intestinal microbiota changed significantly in AIDS diarrhea patients, which affected the immune function of the host. The Xielikang capsule modulated the composition of the intestinal microbiota in AIDS diarrhea patients and thus improved immune function and reduced diarrheal symptoms.